KOMPETENSI KOMUNIKASI ANTARBUDAYA MAHASISWA MELAYU SELATAN THAILAND DALAM BERBAHASA INDONESIA DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA MEDAN - Fauzi Eka Putra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The purpose of this study was to analyze the competency of intercultural communication in Southern Malay Thailand students in Indonesian languages in UINSU Medan. This study using the Theory of Intercultural Communication Competence of Samovar (2010). This research method uses qualitative research which is approaching the hermeneutic phenomenological study. The research subject is Southern Malay Thailand students in UINSU Medan. The Informants were 4 Students which is obtained through Snowball Sampling. Data collection method is observation, interview, and documentation. Analysis of this study is using thematic. The Data Triangulation have done to 3 (Three) indigenous students and 1 (one) Lecturer. The result of this study is showing that Southern Malay Thailand Students have been competency of intercultural communication, which is we can see it from seven (7) components ; experience, motivation, knowledge, mastering the language, attitudes, adopting the intercultural communication and behaviour.The obstacles of this students is only about Language (Bahasa), they’re less mastering the languages so that sometimes they’re missunderstanding the meaning. Another barriers is the speed in talking, the communication in Medan usually have loud voice and high intonation.